Collaborative approaches in initial teacher education: lessons from approaches to developing student teachers’ use of the Internet in science teaching - Sorensen, Peter; Twidle, John; Childs, Ann (Routledge, 2014)
In many countries, governments are keen to persuade teachers at all levels to seek to enhance the learning of their students by incorporating information and communication technologies within their classrooms. This paper reports on the development of collaborative approaches to supporting use of the Internet by Post Graduate Certificate of Education (PGCE) science students on initial teacher education (ITE) courses in England, drawing on data from five higher education institution (HEI)–school partnerships across four years. A mixed-method approach was used, involving questionnaires, structured interviews, lesson observations and case studies. The outcomes of the first three years identified barriers to practice and suggested the need to develop more collaborative approaches to development. The focus of this paper is on examining ways in which university faculty tutors and mentors or cooperating teachers can work together with students on PGCE courses in developing practice. The lessons from this focus on the Internet, no longer a new technology, have enabled us to identify implications for HEI partnerships in ITE and suggest a need for further collaborative structures in order to support and develop practices, including those involving the innovative use of new technologies in the post-industrial society.